Optimization of pretreatment and enzymatic hydrolysis of pineapple leaves fiber for reducing sugar production - Mohd. Nashiruddin, Noor Idayu (2019)
Pineapple leaves fiber (PALF) are classified as an abundant lignocellulosic biofiber material in Asia including Malaysia. Conversion of PALF into reducing sugar has contributed to an alternative use of lignocellulose source especially in the production of value-added product such as amino acid, biofuels and vitamins. In bioconversion process, pretreatment of lignocellulosic biomass is important to enhance the accessibility of enzyme hydrolysis, which can increase the yield of reducing sugar. PALF have a very complex arrangement o f structure thus proper study in pretreatment and enzymatic hydrolysis process is needed to obtain optimum yield of reducing sugar. In this study, PALF pretreated with sodium hydroxide (NaOH) contributed to the optimum yield o f reducing sugar (11.65 mg/mL) which were higher compared to dilute sulphuric acid (8.11 mg/mL) and autohydrolysis pretreatment (6.50 mg/mL). The best pretreatment method of PALF using NaOH had been optimized using response surface methodology with Box-Behnken design. The optimum operating conditions of NaOH pretreatment were found to be at 2.43 % (w/v) of NaOH concentration, 87.22 oC temperature and 57.15 min pretreatment time which produced optimum yield of reducing sugar, 17.26 mg/mL. The optimized pretreated PALF was further hydrolyzed through enzymatic hydrolysis process using cellulase enzyme. The optimum operating conditions for enzymatic hydrolysis were found to be at 228.48 pg/mL of enzyme loading, 45 oC temperature and 69.06 min of hydrolysis time and produced optimum yield of reducing sugar, 108.74 mg/mL, with 84.12 % improvement before an optimization of enzymatic hydrolysis process. The kinetic studies of enzymatic hydrolysis process on pretreated PALF showed good correlation between the influence o f enzyme concentration and substrate on the production of reducing sugar. Chrastil approach shows a good correlation (R2) with all enzyme concentration at 50 pg/mL (0.97), 150 pg/mL (0.94), 200 pg/mL (0.94), 228.48 pg/mL (0.95), 250 pg/mL (0.92) and 300 pg/mL (0.90) while modified Michaelis-Menten model obtain R2 = 0.99. In addition, it also shows that NaOH pretreatment on PALF was able to enhance the movement of molecules in pretreated PALF, thus enhance the reaction of enzyme into substrate. This study has proven that by optimizing the operating conditions of the pretreatment and enzymatic hydrolysis processes, the yield of total reducing sugar extracted from PALF could be enhanced.